Annual international shorebird expeditions to Rio Grande in Tierra del Fuego 2000-2004 - Baker, Allan (2005)
We organized annual expeditions to Rio Grande in Argentinian Tierra del Fuego from 2000 to 2004 to census, capture and band Red Knots Calidris canutus after their arrival on the southern migration from Arctic breeding grounds. The population declined from about 6,000 birds in 2000 to 4,000 in 2004. A total of 2,214 knots were banded, of which 1,787 were adults, 287 immatures and only 140 juveniles. Of 312 retraps, 88 had been banded previously at Rio Grande and the remainder were from localities in South America and Delaware Bay, USA. Average mass of the adults in the 2004 sample was significantly lower than in all other years (p < 0.0028),  consistent with the fact that they had arrived three weeks later arrival at Rio Grande that year. Additionally, in both adults and immatures, average mass in 2002 was significantly lower than in 2000–2001 or 2003. Late arrival of adults in 2004 delayed wing moult and the intensity of body moult relative to other years. Studies of pathogens and parasites, feather isotopes and sex-specific survival are underway to try to elucidate possible additional causes of the severe and continuing population decline in the rufa population of the Red Knot. consistent with the fact that they had arrived three weeks later arrival at Rio Grande that year. Additionally, in both adults and immatures, average mass in 2002 was significantly lower than in 2000–2001 or 2003. Late arrival of adults in 2004 delayed wing moult and the intensity of body moult relative to other years.